2016
DOI: 10.1007/s10151-016-1568-6
|View full text |Cite
|
Sign up to set email alerts
|

Combined NOTES total mesorectal excision and single-incision laparoscopy principles for conservative proctectomy: a single-centre study

Abstract: Combining an endoscopic transanal TME and a single laparoscopic ileostomy-site proctectomy is a promising minimally invasive approach for the treatment of low rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 39 publications
5
23
1
1
Order By: Relevance
“…Six eligible studies investigating single access NOTES have been identified [164169]. The total population consists of 249 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Six eligible studies investigating single access NOTES have been identified [164169]. The total population consists of 249 patients.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, patient characteristics were as follows: 56.52% were male patients, 82.61% had ASA score 2, the median distance from anal verge was 52 mm, the median tumor size was 20 mm, 65.22% were at AJCC clinical stage III, 91.30% were at cT3, and 47.83% were at cN1; the characteristics of our patients were compatible with only one TaTME-SPLS study done in France. [18] Sixty percent of the patients had ISR because their tumor margins were close to dentate line of the anus. The mean operation time was 366 minutes.…”
Section: Resultsmentioning
confidence: 99%
“…[17] When TaTME was performed via the transanal platform, it was di cult to continue upward dissection to reach the descending colon or splenic exure. [17,18] So, the procedures of TaTME, including high ligation of the inferior mesenteric artery and vein and mobilization of the sigmoid colon, descending colon, and splenic exure colon were performed assisted by the traditional laparoscopic surgery or single-port laparoscopic surgery. [17,18] According to our knowledge, there were few case series reports on TaTME assisted by single-port laparoscopic surgery (TaTME-SPLS).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations